1987
DOI: 10.1139/t87-057
|View full text |Cite
|
Sign up to set email alerts
|

Residual strength of smectite-dominated soils from the Kamenose landslide in Japan

Abstract: The residual strength of smectite-dominated soils from the main slip surfaces of the Kamenose landslide, Japan, was measured by ring shear test, and the relations of the residual strength to the clay fraction content and clay particle orientation were studied. The residual angles of shearing resistance, [Formula: see text], were estimated assuming that the residual cohesion is zero. The magnitude of the residual angle of shearing resistance was dependent on the <2-μm clay fraction content, CF, and on the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 8 publications
(18 reference statements)
3
19
0
Order By: Relevance
“…A ring-shear test apparatus is commonly used in investigations of shear strength in the slip surfaces of landslides and fault zones because it can shear a specimen with a unidirectional rotational movement for unlimited relative displacement [10,16,18,19,[21][22][23][24][28][29][30][31][32][33][34][35][36][37][38]. The ring-shear apparatus used in this study was improved at the National Institute of Advanced Industrial Science and Technology (AIST) in Japan.…”
Section: Ring-shear Apparatus and Permeability Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A ring-shear test apparatus is commonly used in investigations of shear strength in the slip surfaces of landslides and fault zones because it can shear a specimen with a unidirectional rotational movement for unlimited relative displacement [10,16,18,19,[21][22][23][24][28][29][30][31][32][33][34][35][36][37][38]. The ring-shear apparatus used in this study was improved at the National Institute of Advanced Industrial Science and Technology (AIST) in Japan.…”
Section: Ring-shear Apparatus and Permeability Measurementsmentioning
confidence: 99%
“…Typically, porosity reduction is associated with grain size reduction and fault slip due to the reorientation of particles [6][7][8][9][10]. Several studies used a ring-shear apparatus with large-displacement shearing to measure permeability evolution [11][12][13][14][15][16], because a ring-shear device can shear a specimen with a large displacement that is similar to natural faults with the same direction of movement for the mobile half of the specimen relative to the stationary half [17][18][19][20][21][22][23][24]. Previous studies found that permeability evolution due to particle crushing is related to porosity reduction [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The residual strength was conventionally determined using RST apparatus (e.g., Bishop et al, 1971;La Gatta, 1971;Bucher, 1975;Bromhead, 1979;Gibo, 1987;Yatabe et al, 1991;Suzuki et al, 1997) and RDBST apparatus (e.g., Nakamori and Sutho, 1988; Okawara et al, 2000a). The RDBST apparatus can apply a large deformation to a specimen by reciprocating the direction of shearing.…”
Section: Test Apparatus and Test Proceduresmentioning
confidence: 99%
“…Subsequently, the specimen was sheared under a constant total normal stress, sN, until the accumulated shear displacement, Sd, became a su‹cient value to reach the residual state. The residual strength of clay is associated with degree of reorientation of soil particles which is aŠected by the normal stress, the shear displacement and so on (Gibo et al, 1987;. Okawara (2000b) described that the degree of reorientation of soil particles parallel to the direction of shearing did not always increase in RDBST if accumulated shear displacement was su‹ciently great.…”
Section: Test Conditions and Test Casesmentioning
confidence: 99%
“…Now, ring shear apparatuses have become essential for soil behavior studies, especially for measuring shear resistance involved in large shear displacement with less ambiguity. Based on ring shear tests, various correlations between residual strengths and soil index properties have been proposed (Lupini et al 1981;Skempton 1985;Gibo et al 1987;Collotta et al 1989;Moore 1991;Di and Fenelli 1994;Stark and Eid 1994;Tika et al 1996;Kamai 1998;Okada et al 2004;Gratchev et al 2006). Together with microstructure analysis of soil, these studies greatly expand people's understanding of the nature of residual strength generation.…”
Section: Introductionmentioning
confidence: 99%